Heuristic algorithm for lot sizing and scheduling on identical parallel machines - Książek, Roger (Decision Making in Manufacturing and Services, 2022)
In this paper a newly developed heuristic algorithm for lotsizing and scheduling on identical parallel machines is presented. A basic concept and an aim of lotsizing and scheduling are described and clarified. Furthermore, models for considered problems for fixed and variable demand as well as for one and many identical parallel machines are presented. A concept and a formal description of newly developed heuristic algorithm is described. The paper includes in details the obtained results and solutions of conducted experiments and the description of used data sets.